Partnerships between Agencies and Transportation Network Companies for Transportation-Disadvantage Populations: Benefits, Problems, and Challenges. Issue 12 (December 2021) - Steiner, Ruth L.; Bai, Xueyin; Bejleri, Ilir; Han, Mengjie; "Jacob" Yan, Xiang
Transportation network companies (TNCs), such as Uber and Lyft, offer a new mobility option to consumers. An increasing number of transit agencies work with TNCs, and different types of partnerships have formed. While these service models may serve the general population well, their implications for transportation-disadvantage populations, including older adults, individuals with disabilities, and low-income people, have not received enough attention. These populations are highly dependent on public transit services. Additionally, we have limited firsthand knowledge of challenges that hinder transit agencies and related human service agencies from building partnerships with TNCs. Can these agency/TNC partnerships accommodate the needs of transportation-disadvantage populations? This study explores these issues through a literature review and interviews with 16 related organizations in the State of Florida, where transportation-disadvantage populations are served through a coordinated system but the partnerships with TNCs are still limited. The paper first categorizes the existing agency/TNC partnership service models into three types and examines their benefits and problems in serving transportation-disadvantage populations. It then identifies different organizations' perceptions of TNCs and the challenges for some agencies to work with TNCs. The general challenges include difficulty in estimating service demand, data sharing problems, hidden costs and staff efforts, training and safety issues, and the need of complementary vendors. The challenges specifically in rural areas are a lack of motivation and commitment among TNCs, affordability issues, and TNCs' adaptation to the rural geography. These challenges in agency/TNC partnerships need to be addressed to serve the public better, including transportation-disadvantage populations.